2015
DOI: 10.1016/j.engfracmech.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the rate dependence of fracture propagation in rocks using digital image correlation (DIC) method

Abstract: Please cite this article as: Gao, G., Yao, W., Xia, K., Li, Z., Investigation of the rate dependence of fracture propagation in rocks using digital image correlation (DIC) method, Engineering Fracture Mechanics (2015), doi: http://dx. ABSTRACTLoading rate is the main controlling factor in dynamic failure of rocks. In this paper, digital image correlation (DIC) combined with ultra-high speed photography is utilized to study the loading rate effect of a granitic rock -Laurentian granite using notched semi-circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Also the loading rate has a strong effect on the fracture strength and fracture toughness of rocks and other brittle materials [1,2]. One of the most obvious engineering applications where both confinement and loading rate have significant roles is the percussive drilling of hard rocks, where the drill hammer impacts the rock at high speed causing extremely high pressures on the rock under the relatively small cross sectional area of the hammer buttons.…”
Section: Introductionmentioning
confidence: 99%
“…Also the loading rate has a strong effect on the fracture strength and fracture toughness of rocks and other brittle materials [1,2]. One of the most obvious engineering applications where both confinement and loading rate have significant roles is the percussive drilling of hard rocks, where the drill hammer impacts the rock at high speed causing extremely high pressures on the rock under the relatively small cross sectional area of the hammer buttons.…”
Section: Introductionmentioning
confidence: 99%
“…Image Correlation to Capture Dynamic Ruptures. The digital image correlation method has been successfully applied in a variety of dynamic applications [88][89][90][91][92][93][94]. However, quantifying with DIC the full-field evolution of dynamic ruptures traveling at speeds in the range of several kilometers per second (typically 1 km/s for a sub-Rayleigh rupture and up to about 2.6 km/s for a supershear rupture) has its own set of challenges, requiring a temporal acquisition on the order of 1-2 MHz, in order to capture the Fig.…”
Section: Challenges In Developing Ultrahigh-speed Digitalmentioning
confidence: 99%
“…Mahanta et al [19] studied the strain rate sensitivity to rock fracture toughness, and the results indicated that, with increasing strain rates, the fracture toughness and tensile strength gradually increased. Previous studies have shown that the parameters of fracture velocity, rock strength, and fracture initiation toughness exhibited significant loading rate dependence [20][21][22][23][24]. However, the conventional monitoring methods, including AE and strain gauge, cannot supply adequate information about crack propagation, which restrict its application.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental investigations of mechanical properties and fracture behaviour of rocks were commonly performed at a macroscopic level [23]. In order to obtain the microcracking and microdeformation characteristics around the crack tip more accurately, combining a microscopic imaging platform with high spatial resolution with the DIC technique is an important trend to further develop rock fracture mechanical experiments [35][36][37].…”
Section: Introductionmentioning
confidence: 99%